Examining Insomnia During Intensive Treatment for Veterans with Posttraumatic Stress Disorder: Does it Improve and Does it Predict Treatment Outcomes?. Issue 4 (26th March 2020) - Zalta, Alyson K.; Pinkerton, Linzy M.; Valdespino‐Hayden, Zerbrina; Smith, Dale L.; Burgess, Helen J.; Held, Philip; Boley, Randy A.; Karnik, Niranjan S.; Pollack, Mark H.
Abstract: Previous research has demonstrated that sleep disturbances show little improvement with evidence‐based psychotherapy for posttraumatic stress disorder (PTSD); however, sleep improvements are associated with PTSD treatment outcomes. The goal of the current study was to evaluate changes in self‐reported insomnia symptoms and the association between insomnia symptoms and treatment outcome during a 3‐week intensive treatment program (ITP) for veterans with PTSD that integrated cognitive processing therapy (CPT), mindfulness, yoga, and other ancillary services. As part of standard clinical procedures, veterans ( N = 165) completed self‐report assessments of insomnia symptoms at pre‐ and posttreatment as well as self‐report assessments of PTSD and depression symptoms approximately every other day during treatment. Most veterans reported at least moderate difficulties with insomnia at both pretreatment (83.0%–95.1%) and posttreatment (69.1–71.3%). Statistically significant reductions in self‐reported insomnia severity occurred from pretreatment to posttreatment; however, the effect size was small, d = 0.33. Longitudinal mixed‐effects models showed a significant interactive effect of Changes in Insomnia × Time in predicting PTSD and depression symptoms, indicating that patients with more improvements in insomnia had more positive treatment outcomes. These findings suggest that many veterans continued to struggle with sleep disruption after a 3‐week ITP, and successful efforts to improve sleep could lead to better PTSD treatment outcomes. Further research is needed to establish how adjunctive sleep interventions can be used to maximize both sleep and PTSD outcomes. Resumen: JOTS‐19‐0048.R3 Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Examinando el Insomnio durante Tratamiento Intensivo para Veteranos con TEPT: ¿Es esto una Mejora y Predice los Resultados del Tratamiento? INSOMNIO Y TRATAMIENTO INTENSIVO DE TEPT Investigaciones anteriores han demostrado que alteraciones del sueño muestran pocas mejoras con terapias basadas en la evidencia para el trastorno de estrés postraumático (TEPT); sin embargo, las mejoras en el sueño están asociadas con resultados de tratamientos para TEPT. El objetivo del presente estudio fue evaluar los cambios del auto reporte de síntomas de insomnio y la asociación entre los síntomas de insomnio y los resultados del tratamiento durante 3 semanas del programa de tratamiento intensivo (PTI) para veteranos con TEPT, el cual integra terapia de procesamiento cognitivo (TPC), mindfulness, yoga y otros servicios complementarios. Como parte del procedimiento clínico estándar, los veteranos (N=165) completaron medidas de auto reporte de síntomas de insomnio antes y posterior al tratamiento, así como también medidas de auto reporte para síntomas de TEPT y depresión aproximadamente cada dos días durante el tratamiento. La mayoría de los veteranos reportaron al menos dificultades moderadas con el insomnio en los dos momentos, antes del tratamiento (83.0%– 95.1%) y posterior al tratamiento (69.1–71.3%). Reducciones estadísticamente significativas en los auto reportes de severidad de insomnio ocurrieron desde el pre‐tratamiento hasta el post‐tratamiento, sin embargo, el tamaño del efecto fue pequeño d = 0.33. Modelos de efectos mixtos longitudinales mostraron un efecto de interacción de cambios en insomnio x tiempo en la predicción de síntomas de TEPT y depresión, indicando que pacientes con mayores mejoras en insomnio tuvieron mejores resultados positivos del tratamiento. Estos hallazgos sugieren que muchos veteranos continúan luchando con alteraciones en el sueño 3 semanas después del tratamiento (PTI), y esfuerzos exitosos para mejorar el sueño pueden ser dirigidos para la mejora en los resultados del tratamiento para el TEPT. Es necesaria investigación más extensa para establecer cómo intervenciones del sueño adicionales pueden ser utilizadas para maximizar ambos resultados de sueño y TEPT. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Examining Insomnia during Intensive Treatment for Veterans with PTSD: Does it Improve and Does it Predict Treatment Outcomes? Traditional Chinese 標題: 檢視為患PTSD的退役軍人而設的密集式治療裡的失眠問題:其有否改善及可否預測療效？ 撮要: 過往研究發現, 在治療創傷後壓力症(PTSD)的實證為本心理治療裡, 睡眠障礙的改善不多。可是, 睡眠改善跟PTSD的療效有關。本研究的目的, 為評估在專為患PTSD的退役軍人而設、為期三星期的密集式治療計劃(ITP)中, 樣本自評的失眠症狀改變以及失眠症狀跟療效的關連。這個ITP結合了認知整理治療(CPT)、正念、瑜珈及其他輔助服務。作為標準的臨床程序, 退役軍人(N = 165)在治療前和後, 進行失眠症狀的自我評估, 亦在療程中, 大約隔天對PTSD與抑鬱症狀進行自我評估。大多數退役軍人在治療前(83.0%– 95.1%)和後(69.1–71.3%), 都至少有中度的失眠問題。從治療前到治療後的期間, 樣本的自評失眠嚴重度改善有統計顯著性, 但效應量小)d = 0.33(。縱貫混合效應模型顯示, 失眠問題的改變跟時間點對預測PTSD與抑鬱症狀有顯著的相互效應, 反映失眠問題有較大改善的樣本會取得更好的療效。結果反映, 很多退役軍人完成三星期的ITP後, 仍受睡眠障礙所困, 而成功改善睡眠問題可達致更好的PTSD療效。未來需有進一步的研究, 檢視我們可如何透過補充形式的睡眠干預, 把針對睡眠和PTSD的療效推至最高。 Simplified Chinese 标题: 检视为患PTSD的退役军人而设的密集式治疗里的失眠问题:其有否改善及可否预测疗效？ 撮要: 过往研究发现, 在治疗创伤后压力症(PTSD)的实证为本心理治疗里, 睡眠障碍的改善不多。可是, 睡眠改善跟PTSD的疗效有关。本研究的目的, 为评估在专为患PTSD的退役军人而设、为期三星期的密集式治疗计划(ITP)中, 样本自评的失眠症状改变以及失眠症状跟疗效的关连。这个ITP结合了认知整理治疗(CPT)、正念、瑜珈及其他辅助服务。作为标准的临床程序, 退役军人(N = 165)在治疗前和后, 进行失眠症状的自我评估, 亦在疗程中, 大约隔天对PTSD与抑郁症状进行自我评估。大多数退役军人在治疗前(83.0%– 95.1%)和后(69.1–71.3%), 都至少有中度的失眠问题。从治疗前到治疗后的期间, 样本的自评失眠严重度改善有统计显著性, 但效应量小)d = 0.33(。纵贯混合效应模型显示, 失眠问题的改变跟时间点对预测PTSD与抑郁症状有显著的相互效应, 反映失眠问题有较大改善的样本会取得更好的疗效。结果反映, 很多退役军人完成三星期的ITP后, 仍受睡眠障碍所困, 而成功改善睡眠问题可达致更好的PTSD疗效。未来需有进一步的研究, 检视我们可如何透过补充形式的睡眠干预, 把针对睡眠和PTSD的疗效推至最高。